Knowledge transfer into sport practice: An empirical user analysis of a sport science website - Sperlich, B.; Wicker, P. (European Journal of Sport Science, 2021)
Transferring scientific knowledge to applied practitioners presents a challenge in sport science. Knowledge transfer, conceptualized as knowledge reuse and knowledge contribution, has mainly been studied in the context of specific topics, projects, or organizations. The purposes of this study were to investigate the determinants of knowledge transfer from a publicly available website to its users and to cluster users into different groups based on their level of knowledge transfer. The website www.sportsandscience.de is dedicated to translating evidence-based knowledge that is regularly generated in scientific studies into short and digestible information through e.g. videos and blogs, and provides opportunities for knowledge reuse and contribution. A theoretical model of knowledge transfer in organizations which was adapted to this context guided the study. Data from an online survey of registered website users were employed for the empirical analysis. The regression analyses showed that knowledge reuse is positively affected by ease of knowledge access and negatively by age. Knowledge reuse, job experience, and male gender have a significant positive effect on knowledge contribution. The findings suggest that the theoretical model is generally applicable to this context, but also highlight differences to the original organizational setting. Cluster analysis yielded three clusters: Frequent users, occasional users, and frequent contributors. Analyses of variances revealed significant differences among clusters regarding computer self-efficacy, job experience, gender, age, employment, interested sports, and conditional skills, but not concerning education and formal qualifications. Implications for improving knowledge transfer of such a website are provided.